Navigasi Masa Depan Kerja: Tinjauan Literatur Sistematis terhadap Model Kerja Hibrida, Determinan Keberhasilan, dan Agenda Penelitian Masa Depan (2020–2025) - Saryadi Saryadi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background: The global transition to hybrid working models has created a significant paradigm shift in post-pandemic organizational management. While offering flexibility, its implementation faces complex challenges regarding productivity and organizational culture. Objective: This study aims to synthesize global literature on hybrid working to identify key success determinants and existing research gaps. Methods: Utilizing a Systematic Literature Review (SLR) method with the PRISMA protocol, this study analyzes 20 selected journal articles from Scopus, Web of Science, and Google Scholar databases published between 2020 and 2025. Findings: The results indicate that the success of the hybrid model heavily relies on two primary pillars: Trust-based Leadership and inclusive technological infrastructure. A